SURFACE MICROHARDNESS OF MICROHYBRID AND NANOCOMPOSITE AFTER STORAGE IN MOUTH WASHES - Manzoor , Sadia; Arooj , Zartashia; Waqas, Mohammad Abi; Irshad, Nadia; Saeed, Asfia; Malik, Aeeza; Sarfaraz, Zenab; Shaukat, Malik Saleem (Journal of Ayub Medical College Abbottabad, 2022)
Background: Dental composites are aesthetic direct restorative material. However, the effect of mouthwashes on the durability of the material is controversial. This study evaluated and compared the influence of mouthwash composition on the surface hardness of nanofilled (Z350XT) and microhybrid (P60) resin composites. Methods: Comparative in-vitro study was conducted over 6 months at Multan Medical & Dental College. Sixty-four disc-shape specimens of each {nanofilled (Z350XT) and microhybrid (P60)} resin composite were prepared and stored in distilled water at 37°C for 24 hours. The baseline microhardness reading (To) was recorded by Vickers micro-hardness tester. Samples were then randomly divided into four groups (n=16) and stored in Listerine Cool Mint, Colgate Plax, Clinica and distilled water (control). The hardness test was repeated after 12 hours and 24 hours of storage. Results: Nanocomposite (Z350XT) had statistically (p<0.01) higher surface hardness. A significant reduction (p‰¤0.05) in microhardness was observed after immersion of samples in mouthwashes. The reduction in surface hardness was dependent on the immersion time and composition of mouthwashes. Listerine Cool Mint (alcohol-based mouthwash) had greatest degradation effect. Conclusion: Mouth rinses negatively impacted the surface microhardness of the tested resin-based materials. Alcohol-based mouthwashes had greater potential for reducing microhardness. Microhybrid composite appears to be a more suitable material for restoring teeth in patients accustomed to using regular mouthwashes.